2016
DOI: 10.1016/j.gca.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and growth of barite within hydrothermal vent deposits from the Endeavour Segment, Juan de Fuca Ridge

Abstract: Hydrothermal vent deposits form on the seafloor as a result of cooling and mixing of hot hydrothermal fluids with cold seawater. Amongst the major sulfide and sulfate minerals that are preserved at vent sites, barite (BaSO 4 ) is unique because it requires the direct mixing of Ba-rich hydrothermal fluid with sulfate-rich seawater in order for precipitation to occur. Because of its extremely low solubility, barite crystals preserve geochemical fingerprints associated with conditions of formation. Here, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 77 publications
5
38
0
Order By: Relevance
“…Numerous studies of modern marine environments have revealed that pelagic barite crystals mostly have uniform size and shape (submicron to 5 µm, subspherical, elliptical crystals), suggesting very stable nucleation and crystal growth environment. Ovoid and hexagonal barite crystals are interpreted as biotic forms of pelagic barite [10,[17][18][19][20]. Hydrothermal marine barite has been extensively studied, and the dominant hydrothermal barite crystal morphologies are well-formed tabular, acicular/radiating tapered, and bladed to dendritic crystals [10,17,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies of modern marine environments have revealed that pelagic barite crystals mostly have uniform size and shape (submicron to 5 µm, subspherical, elliptical crystals), suggesting very stable nucleation and crystal growth environment. Ovoid and hexagonal barite crystals are interpreted as biotic forms of pelagic barite [10,[17][18][19][20]. Hydrothermal marine barite has been extensively studied, and the dominant hydrothermal barite crystal morphologies are well-formed tabular, acicular/radiating tapered, and bladed to dendritic crystals [10,17,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Ovoid and hexagonal barite crystals are interpreted as biotic forms of pelagic barite [10,[17][18][19][20]. Hydrothermal marine barite has been extensively studied, and the dominant hydrothermal barite crystal morphologies are well-formed tabular, acicular/radiating tapered, and bladed to dendritic crystals [10,17,[19][20][21][22]. For example, hydrothermal and cold seep barite will form cross-cutting tabular crystals that form rosette structures [23][24][25], while diagenetic barite typically consists of flat, tabular-shaped crystals [26] or nodules within sedimentary layers [27].…”
Section: Introductionmentioning
confidence: 99%
“…The Ba, Sr, and Pb contents of the hydrothermal sediments correlate strongly (Figure ) suggesting that the same or similar process(es) may be controlling the behavior of these elements. The Sr/Ba of the hydrothermal component of the sediment core samples (0.07) is within uncertainty the same as that of barite from hydrothermal chimneys along the Endeavour segment (0.06) [ Jamieson et al ., ]. The sediment trap samples have somewhat higher Sr/Ba than the sediments collected in push cores or barite, possibly reflecting the existence of some Sr‐rich anhydrite that will not be preserved in sediments deposited on the seafloor (Figure ).…”
Section: Discussionmentioning
confidence: 73%
“… Crossplots of Ba against (a) Pb and (b) Sr for the sediment core (red) and sediment trap (green) samples. The correlation of these element abundances, and the almost identical Sr/Ba of the sediments and barite in hydrothermal chimneys from the Endeavour area [ Jamieson et al ., ], suggests that these elements may all be controlled by the distribution of barite (±other sulfates) in the sediments. The somewhat higher Sr content of the sediment trap samples for a given Ba content probably reflects the existence of anhydrite in these samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation